Glacilacustrine environment of part of the Oak Ridges Moraine, Southern Ontario - Gilbert, Robert (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractGlacilacustrine sediments in a 112 m core recovered from the Oak Ridges Moraine near Vandorf, Ontario are used to assess the environment at the time of deposition. Varves in the upper 23.7 m are of two types: thinner (20-110 mm) varves in groups of 29 and 23 at two levels. These are dominated by deposition of silt in summer, with lesser amounts of laminated silts and sands representing turbidity current deposition. Thicker (0.18-1.02 m) varves at the base and top of the deposit as well as in a group of 27 between the thin varves have a greater fraction in summer of coarser sediment deposited from gravity flows. Winter deposits of both are dominated by the clay- size fraction and most show at least one parting of silt or sand associated with periods of increased meltwater inflow during winter. Carbonate content varies from 25-55 % with the highest proportion in the thinner deposits in winter and in the summer deposits of thin varves. It is proposed that a large, deep (greater than 100 m at least in the early phases) glacial lake was dammed on the Oak Ridges Moraine between the retreating Simcoe and Ontario lobes to the north and south, respectively, and the Niagara escarpment to the west. This lake existed as a relatively stable feature for at least 100 years.